A novel NOTCH1 missense variant in two fetuses with a non‐syndromic conotruncal heart defect from a single family. (10th January 2023) - Zhou, Jie; Dai, Xiaohui; Liu, Hanmin; Zhou, Shu; Wu, Ting; Guo, Nan; Chen, Jiao
Abstract: Aims: We describe two fetuses with conotruncal heart defects (CTDs) (persistent truncus arteriosus and pulmonary atresia/ventricular septal defect, respectively) in a Chinese family whose parents were both healthy. Testing was performed to identify any underlying genetic cause. Materials and Methods: Genomic DNA was extracted from the peripheral blood of the proband's parents and the skeletal muscle tissue of the two aborted fetuses for genetic testing. Results: A heterozygous likely pathogenic missense variant, c.1724G〉C (:p.Cys575Ser), in the NOTCH1 gene (NM_017617.5) was detected in the two affected fetuses but not in the parents, and the next generation sequencing test of the proband's father showed a normal result. It is therefore presumed to result from germline mosaicism in the proband's mother or, less likely, is a recurrent de novo variant in the fetuses. Conclusion: This is the first description of fetal non‐syndromic CTD caused by a variant in NOTCH1 . This report not only expands the gene variant spectrum of CTDs, but also emphasizes the importance of NOTCH1 testing when a fetal of CTD is detected. Key points: What's already known about this topic? Conotruncal heart defects (CTDs) are severe complex congenital heart diseases that have a substantial genetic contribution, with NOTCH1 variation being the main pathogenic factor. What does this study add? We report variants of CTD in two siblings caused by the same novel heterozygous missense NOTCH1 variant despite normal parental NOTCH1 analysis. To our knowledge, this is the first description of fetal non‐syndromic CTD caused by NOTCH 1 variant. The possibility of germline mosaicism further refines reproductive counseling.